IMPROVING THE EFFICIENCY OF STUDENTS' SHORT-DISTANCE RUNNING TECHNIQUES BASED ON AN INNOVATIVE APPROACH (World Bulletin of Education and Learning, 2025)
The article briefly describes how to improve the efficiency of students' short-distance running technique based on an innovative approach.
Keywords: Innovation, student, short distance, sport, technique, speed, strength, reserve, energy, distance.